Music Theory, Historically-Informed Performance, and The Significance of Cities - Adam Krims (Zeitschrift der Gesellschaft für Musiktheorie)
This article examines three recordings from the early heyday of HIP, made around the same time, all of Beethoven’s First Symphony, Op. 21, focusing on its last movement. It isolates the feature of wind/string balance, widely touted at the time as an advantage of the HIP approach, and measures them at key points of the movement; the resulting similarities of two of the recordings, both from London-based performers, and their pronounced divergence from the third, featuring East-Coast American performers, suggests the possibility that music workers (performers, but also engineers, producers, etc.) informed each others’ aesthetic preference and priorities, whether implicitly or explicitly. Recent theories from urban geography are raised in order to explain the kind of location-based learning that may account for such similarities and divergences, showing that ideas nurtured in discussions of urban creativity can contribute quite substantially to the concerns of music theory.